Meta-analysis on efficacy of nicotine replacement therapies in smoking cessation. - Silagy, C; Mant, D; Fowler, G; Lodge, M (1994)
Nicotine-replacement therapy (NRT) by gum, transdermal patch, intranasal spray, or inhalation is expensive but how effective is it? We have done a meta-analysis of controlled trials to see how effects on abstinence rates are influenced by the clinical setting, the level of nicotine dependency, the dosage of NRT, and the intensity of additional advice and support offered. Published or unpublished randomised controlled trials of NRT that have assessed abstinence at least 6 months after the start of NRT were identified and 53 trials (42 gum, 9 patch, 1 intranasal spray, 1 inhaler), with data from 17,703 subjects, were included in the analyses. Use of NRT increased the odds ratio (OR) of abstinence to 1.71 (95% confidence interval 1.56-1.87) compared with those allocated to the control interventions. The ORs for the different forms of NRT were 1.61 for gum, 2.07 for transdermal patch, 2.92 for nasal spray, and 3.05 for inhaled nicotine. These odds were non-significantly higher in subjects with higher levels of nicotine dependence but they were largely independent of the intensity of additional support provided or the setting in which NRT was offered. We conclude that the currently available forms of NRT are effective therapies to aid smoking cessation.